The stone warriors/ / 4. - Northrop, Michael (TombQuest, 2016)
Twelve-year-olds Alex and Renata are on the run from the Order, which is on the brink of creating an army of indestructible stone warriors to carry out their evil schemes. Only the Lost Spells which his mother used to bring Alex back to life can stop them, but undoing the powerful magic that created the chaos that is now loose in Egypt might very well kill him.